Organocatalysis in the Synthesis of Natural Products: Recent Developments in Aldol and Mannich Reactions, and 1,4-Conjugated Additions - Dibello, Estefania; Gamenara, Daniela; Seoane, Gustavo (Current Organocatalysis, 2015)
The use of organocatalysis has simplified and increased the potential of synthetic approaches to natural products. Different aspects, regarding applications and even perspectives of iminium- or enamine-catalysis have been studied in this increasingly developing area during the past decades. Addressing those features, this article aims to give an overview through selected examples, focusing on discussing academic insights of a variety of key reactions such as aldol and Mannich reactions, and 1,4-conjugated additions, as well as applications to the synthesis of natural products, in the period 2012-to date.
Keywords: 4-conjugated addition